2008
DOI: 10.1007/s00247-008-1036-1
|View full text |Cite
|
Sign up to set email alerts
|

The time of onset of abnormal calcification in spondylometaepiphyseal dysplasia, short limb-abnormal calcification type

Abstract: A 1-month-old boy with shortness of extremities on prenatal US was referred to our department with a provisional diagnosis of achondroplasia. His height was normal but he had short extremities and platyspondyly, premature carpal epiphyses on both hands, and short tubular bones with irregular metaphyses on radiographs. Re-evaluation of the patient at the age of 1 year revealed very short height and premature calcification of the costal cartilages and epiphyses. Spondylometaepiphyseal dysplasia (SMED), short lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…6 The reduced chondrocyte proliferation and bone growth found in the ddr2 À/À mouse was compatible with the previously reported extremely abnormal cartilage documented at the costochondral junction of one SMED-SL patient. 1,5,6 The DDR2 gene is a member of the receptor tyrosine kinase [RTK] family and is involved in signal transduction. 10,11 The DDR2 protein consists of an extracellular discoidin domain and a cytosolic tyrosine kinase domain (TK).…”
mentioning
confidence: 99%
“…6 The reduced chondrocyte proliferation and bone growth found in the ddr2 À/À mouse was compatible with the previously reported extremely abnormal cartilage documented at the costochondral junction of one SMED-SL patient. 1,5,6 The DDR2 gene is a member of the receptor tyrosine kinase [RTK] family and is involved in signal transduction. 10,11 The DDR2 protein consists of an extracellular discoidin domain and a cytosolic tyrosine kinase domain (TK).…”
mentioning
confidence: 99%
“…Our third case was reported previously with his clinical findings by Tüysüz et al [2009]. The boy was from Northern Anatolia.…”
Section: Casementioning
confidence: 62%
“…In this study, we present 2 new cases with one of them harbouring a novel variant. In addition, we reviewed a previously reported case by Tüysüz et al [2009] who was found to harbour the same identified truncating pathogenic variant of the other recently reported Turkish child reported by Ürel-Demir et al [2018]. We defined the course and features of this disorder in Turkish patients.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Prenatal ultrasound showing short extremities has been reported in literature. 11 The early manifestations of the condition, along with the use of exome sequencing, permit an early conformation of diagnosis. This will allow for early surveillance for known complications, such as cord compression.…”
Section: Discussionmentioning
confidence: 99%